Uji Tekan Batako Ringan dari Limbah Pengolahan Emas dengan Variasi Komposisi Abu Sekam Padi - Syahrun, Syahrun; Ahzan, Sukainil; Pangga, Dwi (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2019)
[Title: Test Press Concrete of Gold Processing Waste With Variation of Rice Husk Ash Composition]. Lightweight concrete has been made from waste raw materials processing of gold and ash husk of rice with cement as the supporting materials, foam, and ADT. The purposed light brick-making determined the density and compressive strength. Concrete light created by variations in waste processing of gold and ash husk of rice was respectively 10% LPE + 90% ASP, 25% + 75%, 50% + 50%, 75% + 25%, 100% + 0% (in% volume), hardening time for 11 days. Parameter test performed include density test and compressive strength test. Test results showed that the density and the compressive strength of lightweight concrete with a variation of plus gold processing waste and ash husk of rice, the amount of cement on the conditions remained and the drying time for 11 consecutive days, the density of 1.005 gr/cm3, 0.986 gr/cm3, 1.077 gr/cm3, 1.091 gr/cm3, 1.133 gr/cm3 and the compressive strength of 1.34 MPa, 1.16 MPa, 1.77 MPa, 1.03 MPa, 1.29 , The intensity of the density and the compressive strength was influenced by the amount of foam mix, rice husk ash and ADT.